Contemporary challenges and solutions for mobile and multimedia technologies - Khalil, Ismail 1960-; Weippl, Edgar R. (Information Science Reference, 2013)
"This book provides comprehensive knowledge on the growth and changes in the field of multimedia and mobile technologies" - Provided by publisher
Includes bibliographical references
Keywords: Multimedia communications; Mobile computing; Mobile Computing; Multimedia; Aufsatzsammlung